In silico analysis of the rs1803909 polymorphysis of the ANXA2 gene expressed in peripheral blood monocytes and its association with human osteoporosis (Research, Society and Development, 2022)
The objective was to evaluate the possible morphofunctional and protein stability alterations resulting from Tyrosine amino acid changes by a Histidine at position 269, as well as to correlate with the physiological function of the protein and its probable association with human osteoporosis. Through an in silico analysis based on the information available in the NCBI dbSNP (amino acid change and position) and UNIPROT (sequence in the protein) databases. The impacts of the Y269H modification were analyzed from the tools SIFT, Align-GVGD, SNAP and PROVEAN (function and structure), and PolyPhen-2 (nature of the change). In addition, MuPRO tool (stability changes in the protein) were also used. In silico analysis of the rs1803909 polymorphism demonstrated functional alteration (SIFT tool, Score= 0). As well as, it is estimated that amino acid exchange may be related to damaging alterations (PolyPhen-2, Score= 0.993) and associated with modifications in protein function (PROVEAN, Score= -4.015). In addition, structural (Align-GVGD, Score= 83.33, Class C65) and functional (SNAP, Score= 57) impacts were observed. Complementarily, decreased protein stability arising from Y269H alteration was observed by MuPRO tool, ∆∆G= -1.6731749. However, morphofunctional alterations may be connected to damaging processes and the decreased stability of the protein, thus hindering its action. Furthermore, understanding the morphofunctional and stability changes of rs1803909 may aid in the search for early diagnostic genetic and molecular markers for osteoporosis in humans.